Design of experiments and statistical analysis for grouped observations: monograph - Denisov V. I.; Eger K.-H.; Lemeshko B. Yu.; Tsoy E. B. (Novosibirsk, NSTU Publishing house, 2004)
This monograph is devoted to the problems of design of experiments and statistical data processing. Along with well-known methods, new ones, in particular, methods of statistical processing of grouped and partially grouped data, are set forth. Methods, algorithms, and procedures of regression experiment optimal design, estimation of continuous distribution and regression equations unknown parameters as well as testing statistical hypotheses are described. The book is intended for a wide circle of specialists involved in statistical data processing, conducting experimental research (i.e. engineers, economists, biologists, sociologists, etc.) and students in the final years of study majoring in the aforementioned fields.